Implementing the concept of sustainable development: the place and role of the enterprise - Melnyk, Liliya (Skhid, 2016)
The goal of this article is to present the result of the research on the topic of "practical aspects of implementing the concept of sustainable development at the enterprise level". The article reviews the essence of sustainable development, which highlights two important ideas: this involves the development of economic, social and environmental problems; the present generation has a duty to future generations to leave sufficient stocks of social, natural and economic resources so that they can meet their needs. The results illustrate the components of sustainable development through their integration: socio-economic, social, environmental, ecological and economic. The paper presents the process of implementing the concept of sustainable development in the form of chain: individual - the entity (company) - region - state - planet. In this paper a sustainable development of the company interpreted from the perspective of system-integrated approach, and has been described the role and importance of medium, small and micro enterprises in achieving the sustainable development. Using the literature, observations, and judgment, the paper reiterates that practically the concept of sustainable development can be realized by the company on the basis of social responsibility and the many voluntary instruments: quality management systems, environmental management system, management system of health and safety at work, cleaner production, ecolabelling, responsible care, etc.